COMPETITIVENESS OF AGRICULTURAL PRODUCTS ON THE MEAT- DAIRY CHAIN - Sergiu Sorin CHELMU (Ekonomika Poljoprivrede (1979), 2012)
The paper represents an analysis regarding the competitiveness of agricultural products on the meat-diary chain from Romania. Livestock sector is an important sector of national economy in general and agriculture in particular, providing raw material for food and feed people. Revitalizing agriculture is difficult or even impossible without the development of livestock sector, by reconsidering the role and place that this sector must hold in the national economy.